2018
DOI: 10.18553/jmcp.2018.24.6.554
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Guideline-Recommended Initiation of Therapy, Outcomes, and Cost for Patients with Metastatic Non-Small Cell Lung Cancer

Abstract: This study was sponsored by Genentech. Khoury, Michael, Parikh, and Bunce are employed by Genentech. Casebeer, Drzayich Antol, DeClue, Hopson, Li, and Stemkowski are employed by Comprehensive Health Insights, Humana, which was contracted by Genentech to conduct this study. Sehman is employed by Humana. Based on this research, 2 posters were presented at the Academy of Managed Care Pharmacy Nexus 2017 on October 16-19, 2017, in Dallas, Texas. Another poster was also presented at the International Society for Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Clinical practice guidelines (CPGs) are statements that include recommendations based on “a systematic review of evidence and an assessment of the benefits and harms of alternative care options” for assisting “practitioner and patient decisions” [1, 2]. Additionally, CPGs have been shown to improve clinical outcomes [316].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practice guidelines (CPGs) are statements that include recommendations based on “a systematic review of evidence and an assessment of the benefits and harms of alternative care options” for assisting “practitioner and patient decisions” [1, 2]. Additionally, CPGs have been shown to improve clinical outcomes [316].…”
Section: Introductionmentioning
confidence: 99%
“…No increased costs after guideline implementation were detected by CASEBEER et al [126] after multivariate analysis. NEUBAUER et al [132] could even demonstrate lower costs for guideline-concordant care within a period of 1 year after initiation of first-line chemotherapy in NSCLC patients in a regional outpatient US oncology network (1409 patients; average 12-month on/off pathway costs: USD 18 042 versus USD 27 737; on/off cost ratio 0.71, 95% CI 0.64-0.80).…”
Section: Other Considerationsmentioning
confidence: 83%
“…Summary of evidence and overall quality of evidence 15 observational studies were finally selected out of the 754 initially identified abstracts [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137]. To allow clinically meaningful rating of evidence, we defined six subgroups: guideline implementation: 1) all lung cancer, all stages, all therapies; guideline adherence: 2) NSCLC, all stages, surgical resection with or without neoadjuvant/adjuvant therapies; 3) all lung cancer, all stages, all treatment modalities; 4) NSCLC, unresectable stage III, chemo-and/or radiotherapy; 5) NSCLC, all stages, chemotherapy; and 6) SCLC, all stages, all treatment modalities.…”
Section: Problemmentioning
confidence: 99%
“…However, the performance status in this patient was poor, therefore palliative treatment is recommended with consideration of the age and patient's ability to tolerate toxicity of the treatment. 23 Yang et al reported that gastrointestinal metastatic was poor diagnosis with average time of death was 130 days. 3 This report also showed that lung cancer with intestinal metastatic had poor diagnosis which the patient died within 20 days of hospitalization.…”
Section: Discussionmentioning
confidence: 99%